Making millets matter in Madhya Pradesh - Mondal, A.; King, I.O.; Roy, S.; Priyam, S.; Meldrum, G.; Padulosi, S.; Mishra, S. (Centre for Learning on Sustainable Agriculture (ILEIA), 2016)
A decline in minor millet cultivation rings true across much of India. Yet a country wide revival of this cereal crop is in motion. Farmers are again recognising and asserting the value of minor millets, a cereal crop that was once central to their culture. A group of farmers in Madhya Pradesh have taken strength from farmers in Tamil Nadu who have successfully brought millet back into their fields, their homes and onto plates across their region. This is a story of how learning exchanges and partnerships support amplification of succcessful initiatives.